2020
DOI: 10.1080/20009666.2020.1808359
|View full text |Cite
|
Sign up to set email alerts
|

I can’t hear you, you said I had what?: A case report and literature review

Abstract: We report the case of a 46-year old African American woman who presented to the emergency department with one week of progressive bilateral deafness associated with worsening gait abnormalities, visual changes, and confusion. She was diagnosed with Wernicke encephalopathy (WE) attributed to alcohol abuse; her symptoms, including hearing loss, improved with thiamine replacement. WE, a condition due to thiamine deficiency, commonly affects those with alcohol use disorder or gastric bypass history. Though traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Ton et al presented the most recent review of cases of SNHL in WE, which only highlighted one case in which alcohol contributed to the patient's thiamine deficiency 1 . A further literature search has only yielded one other similar case of alcohol‐related thiamine deficiency 3 . We present the third known case of hearing loss in WE related to alcoholism.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Ton et al presented the most recent review of cases of SNHL in WE, which only highlighted one case in which alcohol contributed to the patient's thiamine deficiency 1 . A further literature search has only yielded one other similar case of alcohol‐related thiamine deficiency 3 . We present the third known case of hearing loss in WE related to alcoholism.…”
Section: Discussionmentioning
confidence: 85%
“…1 A further literature search has only yielded one other similar case of alcoholrelated thiamine deficiency. 3 We present the third known case of hearing loss in WE related to alcoholism. Further research is needed to better understand why alcohol represents such a small portion of these cases despite being the most common cause of WE.…”
Section: Discussionmentioning
confidence: 94%
“…Magnetic resonant imaging (MRI) is a reliable test for WE. The reported sensitivity and speci city of MRI for diagnosisof WE are 53% and 93%, respectively [5]. Increased T2-weighted and uid-attenuated inversion recovery (FLAIR) signal intensities in the regions of the periaqueduct, periventricle, and medial thalami are the characteristic features [2].This patient showed typical MRI ndings of symmetric FLAIR hyperintensities in the brain stem, medulla oblongata, bilateral dorsal thalamus, and periventricular region of the third ventricle.…”
Section: Discussion Conclusionmentioning
confidence: 90%
“…MRI is a reliable test for WE. The reported sensitivity and specificity of MRI for the diagnosis of WE are 53% and 93%, respectively [ 14 ]. Increased T2-weighted and FLAIR signal intensities in the periaqueduct, periventricular, and medial thalami regions are the characteristic features [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this patient, DWI restriction was observed in the medial and lateral geniculate bodies, indicating impairment of the visual and auditory pathways. Some studies have demonstrated that MRI has a high specificity but low sensitivity for WE [ 14 , 16 ]. However, a large number of researchers believe that MRI is a powerful and reliable tool that should be used to support the diagnosis of acute WE in both alcoholic and and nonalcoholic individuals [ 5 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%